2009
DOI: 10.2174/157340109787314721
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Culture Model for the Assessment of the Chemopreventive Potential of Dietary Compounds.

Abstract: The study of the mechanisms involved in cell damage mediated by oxidative compounds as well as the evaluation of biomarkers of the cellular antioxidant defence system in such conditions could greatly help to prevent appearance and development of oxidative stress related diseases. The present overview describes a model of oxidative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 89 publications
1
38
0
Order By: Relevance
“…Since the liver is the main target for dietary antioxidants once absorbed from the gastrointestinal tract and the major place for xenobiotic metabolism, studies dealing with the effect of antioxidant dietary compounds at a physiological level in the liver of live animals and at a cellular level in cultured cells from liver origin should be encouraged (Goya et al, 2009). We have previously shown that a cocoa polyphenolic extract containing mainly flavanols (Martín et al, 2010a) as well as Corema album (a berry consumed along the Atlantic littoral of the Iberian Peninsula) (León-González et al, 2012) and green coffee (Baeza et al, 2014) extracts containing mostly hydroxycinnamic acids protect liverderived cells from an oxidative stress by diminishing cell damage and returning the antioxidant defense system to a steady-state activity, which enables the cell to cope with further oxidative insults.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the liver is the main target for dietary antioxidants once absorbed from the gastrointestinal tract and the major place for xenobiotic metabolism, studies dealing with the effect of antioxidant dietary compounds at a physiological level in the liver of live animals and at a cellular level in cultured cells from liver origin should be encouraged (Goya et al, 2009). We have previously shown that a cocoa polyphenolic extract containing mainly flavanols (Martín et al, 2010a) as well as Corema album (a berry consumed along the Atlantic littoral of the Iberian Peninsula) (León-González et al, 2012) and green coffee (Baeza et al, 2014) extracts containing mostly hydroxycinnamic acids protect liverderived cells from an oxidative stress by diminishing cell damage and returning the antioxidant defense system to a steady-state activity, which enables the cell to cope with further oxidative insults.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results demonstrated that treatment of HepG2 cells with t-BOOH was an excellent model of oxidative stress in cell culture (Alía et al, 2006;Goya et al, 2009). As other organic peroxides, t-BOOH can decompose to other alkoxyl and peroxyl radicals in a reaction aided by metal ions that can generate ROS, including H 2 O 2 (Alía et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations